Sensor Coil System for Misalignment Detection and Information Transfer in Dynamic Wireless Power Transfer of Electric Vehicle - Son, Seokhyeon; Shin, Yujun; Woo, Seongho; Ahn, Seungyoung (Journal of Electromagnetic Engineering and Science, 2022)
Wireless power transfer (WPT) technology has been applied to fields as diverse as medical, electronic devices and transportation because of its convenience, safety and aesthetics. In particular, electric vehicles (EVs) that have emerged to replace internal combustion engines, which cause environmental pollution problems, are most suitable for applying WPT. Not only does convenience increase by eliminating charging cables, but the issue of heavy batteries can also be resolved by using dynamic WPT technology, which allows charging of batteries while driving. Furthermore, if dynamic WPT technology and autonomous driving technology are applied together to EVs, the driver’s convenience with regard to charging as well as driving will be greatly improved. In this paper, we propose a multi-purpose sensor coil system for use with dynamic WPT in an EV. Sensor coils detect any misalignment between the source coil and the load coil that occurs while the vehicle is being driven. Furthermore, the proposed system uses sensor coils and ferrite bars to transfer information, such as the lanes which vehicles are being driven. By transferring information, the proposed system can provide the benefits of autonomous driving technology as well as WPT technology. We theoretically analyze the proposed method and confirm that it can play two roles through simulations and experiments.